2011
DOI: 10.1016/j.peptides.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial decapeptide KSL-W attenuates Candida albicans virulence by modulating its effects on Toll-like receptor, human β-defensin, and cytokine expression by engineered human oral mucosa

Abstract: We investigated the toxicity of synthetic antimicrobial decapeptide KSL-W on normal human gingival epithelial cell cultures, its effect on Candida albicans adhesion and growth, and the activation of epithelial cell innate immunity. Our results indicate that KSL-W had no toxic effect on cell adhesion or growth, suggesting its safe use with human cells. Pre-treating C. albicans with KSL-W attenuated the yeast's virulence as demonstrated by its reduced adhesion and growth on engineered human oral mucosa epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…As described by Semlali et al,32,33 RNA (1 μg of each sample) was reverse-transcribed into cDNA using a high-capacity cDNA reverse transcription kit (Applied Biosystems, Warrington, PA, USA). The preparation conditions of the cDNA templates for polymerase chain reaction (PCR) were as follows: 10 minutes at 25°C, 2 hours at 37°C, and 5 minutes at 85°C.…”
Section: Methodsmentioning
confidence: 99%
“…As described by Semlali et al,32,33 RNA (1 μg of each sample) was reverse-transcribed into cDNA using a high-capacity cDNA reverse transcription kit (Applied Biosystems, Warrington, PA, USA). The preparation conditions of the cDNA templates for polymerase chain reaction (PCR) were as follows: 10 minutes at 25°C, 2 hours at 37°C, and 5 minutes at 85°C.…”
Section: Methodsmentioning
confidence: 99%
“…The conditions for the preparation of the cDNA templates for PCR analysis were 5 min at 25°C, 1 h at 42°C, and 5 min at 85°C. Quantitative PCR (qPCR) was carried out as previously described [36]. The quantity of mRNA transcripts was measured with the Bio-Rad CFX96 real-time PCR detection system.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, combined with sub-inhibitory concentrations of benzalkonium chloride, a known cationic surface-active agent [35], KSL was shown to significantly promote bacterial biofilm susceptibility. We also recently demonstrated that KSL-W had a selective effect on C. albicans growth, while exhibiting no toxic effect on epithelial cells [36]. …”
Section: Introductionmentioning
confidence: 99%
“…This ultimately dictates the outcome of pathogenic dissemination [24], [25]. During the development of candidiasis, numerous types of immune cells including neutrophils, tissue macrophages, monocytes and dendritic cells interact with the fungus [26][28]. Most in vitro studies used a single cell type to infection with C. albicans [29], [30].…”
Section: Introductionmentioning
confidence: 99%